Rio, Kyoto, Marrakesh – Groundrules for the global climate policy regime - Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2001)
After four years of intense negotiations that tethered on the brink of failure, the design of the international climate policy regime that is formed by the U.N. Framework Convention on Climate Change, the Kyoto Protocol and the Marrakesh Accords is now sufficiently clear to be implemented. Apart from the U.S. and Australia, all industrialised countries have now stated that they will ratify the Kyoto Protocol. Industrial countries are subject to binding greenhouse gas emissions targets for the commitment period 2008-2012. Several countries profit from exceptions that weaken the targets. The availability of forestry and agricultural sinks will further lower the necessity for emission reductions. A world market for emission rights will form as the Kyoto Mechanisms can be used without limits; the only category apart are sinks CDM credits that are capped. Given the U.S. position to stay out of the Kyoto Protocol, overall demand for emission rights is likely to be lower than supply of "hot air" from Russia and Ukraine. Thus the world market price will be very low, probably between 1 and 5 exteuro / t of CO2. The price could be higher if sellers form a cartel or some sellers are excluded from the market when they do not fulfil the relatively strict reporting rules agreed in Marrakesh. Under a low price the CDM whose institutional structure is rather cumbersome will only have a chance if it concentrates on the cheapest project types and most effective host countries. Especially attractive are projects collecting and burning landfill methane while most renewable energy projects are too expensive, unless they are implemented in very favourable locations. – – Nach vier Jahren aufreibender Verhandlungen ist mit den Beschlüssen von Marrakesch das internationale Klimaregime hinreichend klar, um umsetzbar zu sein. Außer den USA und Australien haben alle Industrieländer angekündigt, das Kyoto-Protokoll zu ratifizieren. Die Industrieländer unterliegen damit für die Verpflichtungsperiode 2008 - 2012 verbindlichen Treibhausgasemissionszielen. Einige Länder werden durch Ausnahmeregeln begünstigt, die die Ziele abschwächen. Die Verfügbarkeit von forst- und landwirtschaftlichen Kohlenstoffsenken wird die Notwendigkeit von Emissionsverringerungen weiter reduzieren. Ein Weltmarkt für Emissionsrechte entsteht mit der unbeschränkten Nutzbarkeit der Kyoto-Mechanismen. Die einzige beschränkte Kategorie sind Senkenkredite des CDM. Vor dem Hintergrund der US-Erklärung, das Protokoll nicht ratifizieren zu wollen, ist die Nachfrage nach Emissionsrechten voraussichtlich geringer als das Angebot an ,,Heißer Luft“ aus Russland und der Ukraine. Daher wird der Weltmarktpreis sehr niedrig liegen, wahrscheinlich zwischen 1 und 5 exteuro pro t CO2. Der Preis könnte höher liegen, falls die Anbieter ein Kartell bilden oder aus dem Markt ausgeschlossen werden, wenn sie den strengen, in Marrakesch vereinbarten Berichtspflichten nicht nachkommen. Bei einem so niedrigen Preis hat der CDM mit seiner relativ schwerfälligen institutionellen Struktur nur dann eine Chance, wenn er sich auf die billigsten Projekttypen und effektivsten Gastländer konzentriert. Besonders attraktiv sind Projekte, die Methan von Müllkippen auffangen und verbrennen, während die meisten Projekte zur Nutzung erneuerbarer Energien zu teuer sind, sofern sie nicht an sehr günstigen Standorten stattfinden.
Keywords: 330; International climate policy; Kyoto Protocol; Marrakesh Accords; sinks; Kyoto Mechanisms; emissions trading; CDM; Klimaschutz; Umweltabkommen; Internationale Umweltpolitik; Kohlendioxid; Luftreinhaltung; Welt